DUKUNGAN KOMUNIKASI INTERPERSONAL GURU DAN MOTIVASI BELAJAR SISWA TERHADAP PRESTASI BELAJAR MATA PELAJARAN SISTEM BAHAN BAKAR SISWA KELAS XII TEKNIK KENDARAAN RINGAN SMK NEGERI 1 CANGKRINGAN YOGYAKARTA TAHUN PELAJARAN 2016/2017 - Bani Israil; Tarto Sentono (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aimed to know: (1) teacher’s interpersonal communication support and learning motivation toward learning achievement of ignition system; (2) teacher’s interpersonal communication support toward learning achievement of ignition system; and (3) learning motivation toward learning achievement of ignition system. The type of this study was ex-post facto. Data collection techniques used questionnaires and documentation. Data analysis technique used descriptive analysis, the first hypothesis testing used double regression analysis, and the second and third hypothesis testing used partial correlation. This study shows that (1) there a positive and significant support of teacher’s interpersonal communication and learning motivation toward learning achievement of ignition system with the score of Freg = 6.633 and significance score 0.003 < 0.05. The score of coefficient correlation (R2) was 0.197, it was meant that teacher’s interpersonal communication and learning motivation gave contribution toward learning achievement of ignition system 19.7%; (2) there a positive and significant support of teacher’s interpersonal communication support toward learning achievement of ignition system; with the score of rx1y-2= 0.328 with the significance score 0.014 < 0.05and (3) there a positive and significant support of learning motivation toward learning achievement of ignition system with the score of rx2y-1= 0.324 with the significance score 0.000 < 0.05.